2008
DOI: 10.1002/gps.2052
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of neuropsychiatric syndromes in demented and psychotic institutionalized elderly

Abstract: The syndrome taxonomies are consistent with the diagnostic criteria. The clinical use of syndrome co-occurrence could help to further understand and evaluate behavioral changes in pharmacological and non-pharmacological treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Thus, delusions and hallucinations have been consistently grouped in a “ psychosis ” sub-syndrome in all factor analytical studies using the NPI. A distinct “ mood ” or “ affective ” cluster (depression and anxiety) has been reported by some studies (Aalten et al, 2007; Zuidema et al, 2007; Dechamps et al, 2008; Savva et al, 2009; Kang et al, 2010; Spalletta et al, 2010), while these symptoms have been included in different sub-syndromes by other authors (e.g., psychosis, agitation; Fuh et al, 2001; Mirakhur et al, 2004). A less reliable factor characterized by high levels of agitation, aggression , and aberrant motor behavior has emerged in several studies under various names (e.g., agitation, hyperactivity, frontal) (Frisoni et al, 1999; Aalten et al, 2003) presenting with heterogeneous psychopathological structure and suggesting that psychomotor features co-occur with psychotic and/or affective symptoms.…”
Section: Symptoms Interrelation and Evolutionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, delusions and hallucinations have been consistently grouped in a “ psychosis ” sub-syndrome in all factor analytical studies using the NPI. A distinct “ mood ” or “ affective ” cluster (depression and anxiety) has been reported by some studies (Aalten et al, 2007; Zuidema et al, 2007; Dechamps et al, 2008; Savva et al, 2009; Kang et al, 2010; Spalletta et al, 2010), while these symptoms have been included in different sub-syndromes by other authors (e.g., psychosis, agitation; Fuh et al, 2001; Mirakhur et al, 2004). A less reliable factor characterized by high levels of agitation, aggression , and aberrant motor behavior has emerged in several studies under various names (e.g., agitation, hyperactivity, frontal) (Frisoni et al, 1999; Aalten et al, 2003) presenting with heterogeneous psychopathological structure and suggesting that psychomotor features co-occur with psychotic and/or affective symptoms.…”
Section: Symptoms Interrelation and Evolutionmentioning
confidence: 84%
“…Particularly, the relation between apathy (highly prevalent in dementia) and the “ mood ” sub-syndrome remains unclear. Studies conducted on outpatients (Aalten et al, 2008; Spalletta et al, 2010) and in nursing-homes (Zuidema et al, 2007; Dechamps et al, 2008; Selbæk and Engedal, 2012) support that apathy and depression are distinct phenomena and belong to different neuropsychiatric syndromes. However, other studies group both symptoms in the same factor (Frisoni et al, 1999; Aalten et al, 2003; Hollingworth et al, 2006).…”
Section: Symptoms Interrelation and Evolutionmentioning
confidence: 98%
“…Subsequent reports of the internal consistency of the NPI were mainly conducted using the newer 12-domain version NPI and also the NPI-NH. Studies reported an α-range of 0.67–0.8 in terms of the NPI’s internal consistency 3,18. Overall, the NPI can be said to have reasonable to good internal consistency.…”
Section: Psychometric Propertiesmentioning
confidence: 99%
“…For example, patients with frontotemporal dementia exhibited significantly more apathy, disinhibition, euphoria, and aberrant motor behavior than those with AD, and patients with progressive supranuclear palsy had significantly more apathy and less agitation and anxiety than those with AD. Patients with vascular dementia were more likely to have depression and less likely to have delusions, and patients with dementia with Lewy bodies more often exhibited delusions and hallucinations than patients with AD 18. In a report from the European Alzheimer Disease Consortium,31 cross-sectional data of 2,354 patients with AD using the NPI for assessment of neuropsychiatric symptoms were collected from 12 centers.…”
Section: Profiling Neuropsychiatric Features Among Different Neurologmentioning
confidence: 99%
“…Though BPSD represents a heterogeneous cluster of symptoms that can be difficult to characterize into more specific sub-syndromes, three primary sub-syndromes have emerged: psychosis (hallucinations and delusions), affective (depression and anxiety), and agitation (agitation and irritability) that have been found to remain relatively stable over time in long-term care residents (Dechamps, Jutland, Onifade, Richard-Hartson, & Bourdel-Marchasson, 2008;Selbrek & Engedal, 2012). Still, others describe greater overlap in the symptoms included in these sub-syndromes (Mirakhur, Craig, Hart, McIlroy, & Passmore, 2004), which is more consistent with our findings.…”
Section: Structural Representation Of Depression Anxiety and Agitationmentioning
confidence: 99%